The study of density and altitudinal distribution of crimson-headed partridge (haematortyx sanguiniceps) and red-breasted partridge (arborophila hyperythra erythrophrys) in Kinabalu Park, Sabah Nur - Nur Syamimi Makbul (2018)
Crimson-headed Partridge Haematortyx sanguiniceps (CHP) and Red-breasted Partridge Arborophila hyperythra erythrophrys (RBP) are the only bird species of Phasianidae that are present in the montane forest of Kinabalu Park. Based on past records, there was no study or research that had been carried out for these two species in Kinabalu Park. Both species are endemic to Borneo and their population trends are declining due to habitat loss and degradation of forest caused by human activities as well as hunting. The objectives of this study are 1) to determine the density of these species along an altitudinal gradient at Mount Kinabalu, Sabah 2) to describe the activity pattern of both species in Kinabalu Park, Sabah and 3) to compare habitat use of the two species in Kinabalu Park. Bird species detection was based on direct and indirect observations. Surveys were conducted by walking quietly along transects within sampling sites at different types of altitudes range in Kinabalu Park. The ranges were 600 m - 1000 m a.s.l, 1500 m - 1800 m a.s.l and 1800 m - 3100 m a.sl. Both partridges occurred at 1500 m until 1900 m a.s.l and there was no call or sighting of them during data sampling in low elevation (600 m – 1000 m a.s.l). The highest mean detection of CHP was within the elevation range of 1500 m a.s.l until 1720 m a.s.l; 9.50 ± 2.89 per visit/km². The highest mean detection of RBP was at 1800 m until 1900 m a.s.l with 3.14 ± 2.34 per visit/km². Both species had the lowest mean detection at 1900 m until 3100 m a.s.l; 0.23 ± 0.31 per visit/km² for CHP and 0.29 ± 0.44 per visit/km² for RBP. At these elevation range, the detection rate for both species was highly variable for each visit. Kruskal-Wallis test had shown that there was a significant difference in density of CHP between trails but not for RBP. Mann-whitney U-test also implied that there were significant differences in density of CHP within the forest types. In fact, the elevation use of these partridges is different significantly as RBP had higher detection at UMF area. In term of activity pattern, both species are almost vocal all day (83%, n=10 hr) and most calling were heard from 0700 hour until 0900 hour. In term of habitat use, Spearman rank correlation test had shown that, the presence of CHP and RBP along elevational range of Mount Kinabalu was not significantly influenced by the habitat variables. Both partridges are considered sympatric as they do utilize similar feeding and roosting grounds but the movement of CHP around the mountain forest area was concentrated within the altitude of 1500 m-1800 m compared to RBP. So far, there was no sign of competition for space and food between these sympatric species in Kinabalu park as its forest area still provides a suitable habitat for them and able to support stable populations of its flora and fauna.